PENGEMBANGAN PEMBELAJARAN MULTIMEDIA INTERAKTIF BERBASIS ISPRING SUITE MATERI KEBERAGAMAN MAKHLUK HIDUP DI LINGKUNGANKU KELAS IV SEKOLAH DASAR - Anwar, Moh. Farid N.; Rozhana, Kardiana Metha; Wulandari, Erika (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2024)
The purpose of this research is to develop valid and effective Ispring Suite-based interactive multimedia learning media on natural science material, theme 3 caring for living things, sub-theme 2 the diversity of living things in my environment, learning 1, class IV. This research is a borg & gall research model consisting of Research and Information Collecting, Planning, Develop Preliminary From Product, Design Validation, Product Revision, Preliminary Field Group Small Testing, Product Revision, Preliminary Large Group Field Testing, The Final Product Is Valid And Effective. . This research was conducted in class IV elementary school. Data validation and questionnaires were analyzed descriptively qualitative. The instruments used were validation questionnaires for material experts, media experts and language experts, student and teacher response questionnaires and learning achievement tests. Based on the research results, the developed learning media has been tested valid by material experts with a validity percentage of 66%, media experts with a percentage of 68%, and linguists with a percentage of 80%. The percentage of mastery of learning outcomes tests with a percentage of 100%. From the results of this study, it can be concluded that the developed media is suitable for use in thematic learning.